2017
DOI: 10.1177/1729881417724190
|View full text |Cite
|
Sign up to set email alerts
|

An optimum strategy for robotic tomato grasping based on real-time viscoelastic parameters estimation

Abstract: It is a challenging task to achieve rapid and stable grasping of fruit and vegetable without damages for the agricultural robot. From the point of view of which most of fruits and vegetables are viscoelastic material, the viscoelastic characteristic of tomato was analyzed based on Burgers model in this article to provide a reference for the robotic grasping. First, the realtime viscoelastic parameters estimation model based on back-propagation neural network was established. The 3-11-4 network structure was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The outcomes of the fitting process notably revealed that the coefficient of determination (R 2 ) surpassed 0.99 for all fittings, confirming the efficacy of the selected model. Similar conclusions were found in the study by Tao et al [34]. The shape of the creep behavior curve is profoundly influenced by the developmental stage of tomatoes, as illustrated in Figure 6.…”
Section: Creep Testsupporting
confidence: 89%
“…The outcomes of the fitting process notably revealed that the coefficient of determination (R 2 ) surpassed 0.99 for all fittings, confirming the efficacy of the selected model. Similar conclusions were found in the study by Tao et al [34]. The shape of the creep behavior curve is profoundly influenced by the developmental stage of tomatoes, as illustrated in Figure 6.…”
Section: Creep Testsupporting
confidence: 89%
“…Agriculture Robots are already investigated in the precision farming topic. Recent research in this area covers the adaptability of robot design to the agriculture sector, the improvement of navigation conditions through additional sensing [82,83,203] and localization capabilities as well as real-time image processing [84,85] and camera detection [86] to maximize the operational capabilities and behaviour of robots and collaborative robots (cobots). Robots can assist humans [87,88] for difficult tasks or replace them for difficult ones.…”
Section: -Precision Farming Techniques and Robot Developmentmentioning
confidence: 99%
“…Nevertheless, the traditional methods, such as tactile, visual, and visuo‐tactile servoing methods consider the physical properties [12] limiting its robustness over the data‐driven learning‐based methods for grasping soft fruits. Supervised learning‐based identification of grasp locations from an image was presented [13, 14] predicted grasp locations without severe overfitting via Convolution Neural Network (CNN).…”
Section: Introductionmentioning
confidence: 99%